MedBulletin - Tauseef, Zahra; Chen, Jacqueline; Wang, Fan Ze; Dong, Audrey (The Meducator, 2022)
Summaries of current news regarding: artificial intelligence in early sepsis detection, glucocorticoids and COVID-19, a novel intervention for advanced prostate cancer, and CAR T-cell therapy for novel treatment of relapsed acute myeloid leukemia.